Sex-Based Differences in Outcomes With Percutaneous Transcatheter Repair of Mitral Regurgitation With the MitraClip System: Transcatheter Valve Therapy Registry From 2011 to 2017. (November 2021) - Villablanca, Pedro A.; Vemulapalli, Sreekanth; Stebbins, Amanda; Dai, Dadi; So, Chak-yu; Eng, Marvin H.; Wang, Dee Dee; Frisoli, Tiberio M.; Lee, James C.; Kang, Guson; Szerlip, Molly; Ibrahim, Homam; et al.
Abstract : Background: Women have a higher rate of adverse events after mitral valve surgery. We sought to evaluate whether outcomes after transcatheter edge-to-edge repair intervention by sex have similar trends to mitral valve surgery. Methods: The primary outcome was 1-year major adverse events defined as a composite of all-cause mortality, stroke, and any bleeding in the overall study cohort. Patients who underwent transcatheter edge-to-edge repair for mitral regurgitation with the MitraClip system in the Society of Thoracic Surgery/American College of Cardiology Transcatheter Valve Therapy registry were evaluated. Linked administrative claims from the Centers for Medicare and Medicaid Services were used to evaluate 1-year clinical outcomes. Associations between sex and outcomes were evaluated using a multivariable logistic regression model for in-hospital outcomes and Cox model for 1-year outcomes. Results: From November 2013 to March 2017, 5295 patients, 47.6% (n=2523) of whom were female, underwent transcatheter edge-to-edge repair. Females were less likely to have >1 clip implanted ( P <0.001) and had a lower adjusted odds ratio of device success (adjusted odds ratio, 0.78 [95% CI, 0.67–0.90]), driven by lower odds of residual mitral gradient <5 mm Hg (adjusted odds ratio, 0.54 [CI, 0.46–0.63]) when compared with males. At 1-year follow-up, the primary outcome did not differ by sex. Female sex was associated with lower adjusted 1-year risk of all-cause mortality (adjusted hazard ratio, 0.80 [CI, 0.68–0.94]), but the adjusted 1-year risk of stroke and any bleeding did not differ by sex. Conclusions: No difference in composite outcome of all-cause mortality, stroke, and any bleeding was observed between females and males. Adjusted 1-year all-cause mortality was lower in females compared with males.